The cephalic labial gland secretions of two socially parasitic bumblebees Bombus hyperboreus ( Alpinobombus ) and Bombus inexspectatus ( Thoracobombus ) question their inquiline strategy - Brasero, Nicolas; Martinet, Baptiste; Lecocq, Thomas; Lhomme, Patrick; Biella, Paolo; Valterova, Irena; Urbanová, Klára; Cornalba, Maurizio; Hines, Heather; Rasmont, Pierre (Insect Science, 2018)
International audience The cephalic labial gland secretions of two socially parasitic bumblebees Bombus hyperboreus (alpinobombus) and Bombus inexspectatus (thoracobombus) question their inquiline strategy